The effectiveness of the printed books as a learning material in a one-day the molecular biology course - Hanum Isfaeni; Aloysius Duran Corebima; Hadi Suwono; Fatchur Rohman (Biosfer: Jurnal Pendidikan Biologi, 2018)
The purpose of this research was to determine the effectiveness of the enrichment book of Conservation Biology Lecture based on normalized gain assessment. The assessment of a lecture can be carried out in the learning process for one. Normalized gain on a class average can be used to make learning assessments. In this assessment, it is expected that the effectiveness of using books as learning media can be achieved by using the normalized gain values. The learning media in this research were printed enrichment books on molecular biology lecture. In this research, it was found that the average score of normalized gain (g) was 0.37 Â± 0.03 (moderate). Thus, the results of the assessment show that the book media as a medium for learning material enrichment in the molecular biology lecture is quite effective.